Conceptual and Application of Properties of Integer Operations in Elementary School Mathematics Learning - Sari, Novita (Generasi, 2026)
Backround: Integers constitute one of the fundamental concepts in mathematics and play an important role in everyday life as well as in elementary school mathematics learning. A solid understanding of integers is essential because it forms the basis for learning more advanced mathematical concepts. However, many students still encounter difficulties in understanding the concept of integers and performing integer operations.Objective: This study aims to analyze the concept of integers, the properties of integer operations, and their implementation in mathematics learning.Method: The research employed a literature review method by examining various books and scientific journals related to mathematics education.Result: The results of the analysis indicate that students’ understanding of integers can be improved through contextual learning approaches, the use of concrete learning media, and a systematic explanation of the properties of integer operations. These findings highlight the importance of designing meaningful learning experiences that connect mathematical concepts with students’ real-life situations.Implication: This study concludes that a strong conceptual understanding of integers is crucial for elementary school students and can be effectively supported through contextual teaching strategies and the use of appropriate instructional media.